Symmetry energy and neutron pressure of finite nuclei using the relativistic mean‐field formalism. Issue 1 (14th February 2021) - Biswal, Nibedita; El Sheikh, M. K Abu; Behera, Deepanjali; Biswal, Subrat Kumar; Patra, Suresh Kumar; Yusof, Norhliza; Kassim, Hassan Abu; Carlson, Brett Vern; Bhuyan, Mrutunjaya
Abstract: The present study investigates the isospin and Z‐dependency of the effective symmetry energy and its co‐efficient, namely, neutron pressure for the isotonic chain of neutron magic N = 40, and 82. The relativistic mean‐field model with the non‐linear NL3 * parameter and Relativistic‐Hartree‐Bogoliubov approach with density‐dependent DD‐ME2 parameter sets are used for the analysis. The coherent density fluctuation model and Liquid‐Drop‐Approximation are adopted to formulate the nuclear matter observables such as symmetry energy, neutron pressure of finite nuclei at local density. We found a notable sign of the shell/sub‐shell closure following the proton magic over the isotonic chain. Further, a comparative analysis shows that the coherent density fluctuation model is a better approximation to include the surface effect of finite nuclei as compared to the Liquid‐Drop‐Approximation, which plays a significant role to determine the shell/sub‐shell closure over an isotopic and/or isotonic chain.